Sensitivity Analysis of Some Key Factors on Turbulence Models for Hydrogen Diffusion Using HYDRAGON Code - Saeed, Muhammad; Zhong, Xianping; Yu, Jiyang; Zhang, Xiaolong; Abdalla, Aniseh Ahmed Atef (Frontiers in Energy Research, 2020)
In this paper, we have investigated the influence of air-fountain injection to study the hydrogen diffusion behavior with the help of 3-Dimensional code, HYDRAGON. Three different turbulence models i. e., Standard k −, model, Re-Normalized Group k − m model and Realizable k − e model have been studied carefully and the comparison of simulated data with experimental data were performed. The effect of air-injection was examined using three different velocities i.e., 0.411, 2.803, and 5.143 m/s to evaluate the phenomena of stratification break-up. When we kept the velocity of the air-injection as low as 0.411 m/s, the simulated results obtained through these three turbulence models were very close to experimental data. As the velocity was set to 5.143 m/s, the simulated data captured the experimental data well. But, when the velocity of air-injection was kept 2.803 m/s, the two turbulence models i.e., SKE and RNG turbulence models gave satisfactory results. However, when we added the turbulent diffusivity coefficient to RNG and RLZ turbulence models in the HYDRAGON code, a minor influence was investigated in these simulation results.